Roadblock to Innovation: The Role of Patent Litigation in Corporate R&D - Mezzanotti, Filippo (Management Science, 2021)
I examine how patent enforcement affects corporate research and development (R&D), exploiting the legal changes induced by the Supreme Court decision eBay v. MercExchange. This ruling increased courts’ flexibility in remedying patent cases and effectively lowered the potential costs of patent litigation for defendants. For identification, I compare innovative activity across firms differentially exposed to patent litigation before the ruling. Across several measures, I find that the decision led to a general increase in innovation. This result confirms that the changes in enforcement induced by the ruling reduced some of the distortions caused by patent litigation. Exploring the channels, I show that patent litigation negatively affects investment because it lowers the returns from R&D and exacerbates its financing constraints. This paper was accepted by Gustavo Manso, finance.